Active and Protected: Developing a “Safer Sex” Handout for Adolescents and Young Adults with Cancer - McGrady, Meghan E. (J Adolesc Young Adult Oncol, 2021)
There is a critical need to engage adolescents and young adults (AYAs) with cancer in conversations regarding “safer” sexual activity during treatment. Many providers, however, report lacking the knowledge and/or tools to engage in these discussions. This article describes the experience of one pediatric institution in assessing and addressing provider barriers to safer sexual activity discussions among AYAs with cancer. Feedback from patients and providers resulted in an educational handout detailing recommendations regarding safer sex practices for AYAs with cancer. Handout adoption, acceptability, appropriateness, and feasibility are described alongside barriers to assist other institutions seeking to develop similar interventions.